Direct Design of Stainless Steel Frames: Recommendations and Case Studies. Issue 4 (14th September 2022) - Arrayago, Itsaso; Rasmussen, Kim J.R.; Zhang, Hao; Real, Esther
Abstract: Acknowledging the potential of system‐based design approaches, most international design standards for steel structures include preliminary versions of such alternative design methods. The Direct Design Method (DDM) is one of these approaches, which allows designing steel structures directly using advanced numerical analyses without requiring further member checks. This paper presents the DDM design (and verification) procedure and summarizes the key aspects of the advanced finite element model necessary for the determination of the system strength, with an emphasis on cold‐formed stainless steel portal frames. Through the design of two frames, the DDM design procedure is illustrated and the resulting cross‐sections are compared with those derived using the traditional two‐step design approach in the Eurocode and ASCE design frameworks. The results demonstrate that the DDM verification process is simpler and more direct, and that lighter structures are obtained when designing using the DDM for strength considerations. Finally, this paper also highlights that allowing larger deformations in the ultimate limit state design for the DDM does not have additional negative effects on the serviceability requirements if compared to the traditional two‐step design approach.